2012
DOI: 10.1109/tbme.2011.2168397
|View full text |Cite
|
Sign up to set email alerts
|

Influence of <formula formulatype="inline"><tex Notation="TeX">${I_{Ks}}$</tex></formula> Heterogeneities on the Genesis of the T-wave: A Computational Evaluation

Abstract: Despite the commonly accepted notion that action potential duration (APD) is distributed heterogeneously throughout the ventricles and that the associated dispersion of repolarization is mainly responsible for the shape of the T-wave, its concordance and exact morphology are still not completely understood. This paper evaluated the T-waves for different previously measured heterogeneous ion channel distributions. To this end, cardiac activation and repolarization was simulated on a high resolution and anisotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 58 publications
5
72
1
2
Order By: Relevance
“…Often, the transmural and apicobasal gradients are alternatively considered as a major contributor to the generation of the T-wave. In accordance with the previous simulations [12,16], the present results showed that if equally expressed, the two gradients (as well as the interventricular gradient) produced the similar body surface potential distributions. The analysis of the contribution of the different parts of the ventricles to the resultant repolarization vector revealed that the transmural gradient produced substantial but oppositely directed transversal T-vectors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Often, the transmural and apicobasal gradients are alternatively considered as a major contributor to the generation of the T-wave. In accordance with the previous simulations [12,16], the present results showed that if equally expressed, the two gradients (as well as the interventricular gradient) produced the similar body surface potential distributions. The analysis of the contribution of the different parts of the ventricles to the resultant repolarization vector revealed that the transmural gradient produced substantial but oppositely directed transversal T-vectors.…”
Section: Discussionsupporting
confidence: 93%
“…In view of the fact that the mass of the septum is comparable with the left ventricular free wall mass, the septum could contribute much to the resulting repolarization gradient. The experiments, as well as computer simulations, showed that both the transmural and the apicobasal APD gradients can generate concordant T-waves and body surface potential distributions [5,12,16]. However, it remains unclear how the two different gradients can produce the similar electric field.…”
Section: Introductionmentioning
confidence: 98%
“…Three-dimensional anatomical models of the cardiac ventricles and atria have also been constructed. [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Simulations using sophisticated soware and numerical techniques have been conducted to investigate the effect of drugs, disease or mutations at the ionic level on the electrical activity of the human heart. 13,24,27,30,34 10.…”
Section: State-of-the-art Computational Cardiac Electrophysiologymentioning
confidence: 99%
“…Previous cardiac simulation implementations are limited in biophysical detail of the cellular models, size of the model structure (e.g., rabbit vs. human heart), spatial resolution, and practical length of simulation time. Published scientific studies typically cite spatial resolutions of 0.2 to 0.3 mm and 20 to 32 million active elements [19][20][21][22] and simulation times of at most tens of heartbeats. To address these limitations, we have developed Cardioid, a high-performance cardiac simulation tool with detailed cell representations and support for heart geometries with near-cellular spatial resolution based on full-size human ventricle anatomy [23].…”
Section: Qbox On Sequoiamentioning
confidence: 99%